Peningkatan Visibilitas UMKM Desa Nusawungu melalui Pembuatan Titik Lokasi di Google Maps - Ulil Albab; Afrina Syafriyanti; Kurnia Anoem Milandea; Anisah Fitri; Raissa Aldora; Amelia Kartika; Mardiasyah Mardiasyah; Meitha Yesi Rahmawati; Ika Yulida Hakim (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
This community service program aims to enhance the visibility and competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in Nusawungu Village through the creation of business location pins on Google Maps. The background of this initiative lies in the main challenges faced by local entrepreneurs, namely limited access to marketing channels and low digital exposure. Many businesses have been operating for years but remain difficult to find due to the absence of a clear digital identity, particularly on online maps. Therefore, this program focuses on utilizing Google Maps as an effective, low-cost, and accessible promotional medium. The program adopts the Participatory Action Research (PAR) method, emphasizing the active involvement of MSME actors in each implementation stage. The process began with mapping and collecting data on existing businesses, followed by classifying them into categories such as culinary, crafts, services, and trade. The next steps included filling in complete addresses, determining accurate coordinates, and uploading business and product photos. Verification of Google Maps profiles was then carried out to ensure that the businesses became officially accessible to the public. Furthermore, participants received guidance on adding supporting information, including operating hours, contact numbers, and social media links. The results demonstrated that all registered MSMEs successfully created active Google Maps profiles with complete information. The outcomes include increased consumer accessibility in locating businesses, recognizing available products or services, and directly contacting owners. This implementation has proven to make a significant contribution to market reach expansion and the strengthening of digital marketing strategies without requiring additional financial costs. These findings align with previous studies affirming the effectiveness of Google Maps as a promotional tool and a means of empowering MSMEs in rural areas. Moreover, this initiative opens opportunities for further development through integration with other digital platforms.